2012
DOI: 10.4040/jkan.2012.42.5.689
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effectiveness of a Drug Dosage Calculation Training Program using Cognitive Loading Theory based on Smartphone Application

Abstract: Purpose: This study was done to develop and evaluate a drug dosage calculation training program using cognitive loading theory based on a smartphone application. Calculation ability, dosage calculation related self-efficacy and anxiety were measured. Methods: A nonequivalent control group design was used. Smartphone application and a handout for self-study were developed and administered to the experimental group and only a handout was provided for control group. Intervention period was 4 weeks. Data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Self-efficacy in drug knowledge and dosage calculation improved in two studies [ 19 20 ], but efficacy in Foley catheterization skills did not improve in students who used their smartphones for practice [ 15 ]. Communication competency using smartphone video clips [ 21 ] and academic motivation using smartphone applications (Kakao Talk) [ 22 ] significantly increased in the experimental group of students during the classroom activities.…”
Section: Resultsmentioning
confidence: 99%
“…Self-efficacy in drug knowledge and dosage calculation improved in two studies [ 19 20 ], but efficacy in Foley catheterization skills did not improve in students who used their smartphones for practice [ 15 ]. Communication competency using smartphone video clips [ 21 ] and academic motivation using smartphone applications (Kakao Talk) [ 22 ] significantly increased in the experimental group of students during the classroom activities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study reports on how prompt access to the medication and medical information using a mobile device enhances self-efficacy of students [11]. Moreover, competency is enhanced when the medication calculation exercise application is used through the cognitive load theory [13]. In addition, previous studies reported that when smartphone-based communication technologies [14] are applied to learn nursing skills, nursing competency is enhanced effectively [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated based on Kim, Park, and Park (2012). A power analysis for a t-test was performed using an alpha coefficient of 0.05, beta of 0.20, and effect size of 0.20.…”
Section: Population and Samplementioning
confidence: 99%
“…The smartphone-based app for this study was developed by the research team. Analysis of learners and their environment, designs for templates and contents, program development, and evaluation by informatics experts were performed, and the effectiveness and validity were proved in a previous study (Kim et al, 2012). The smartphone-based app adopted a cognitive-load theory and contained two pages; a principle learning page and a practical game page.…”
Section: Development Of Interventionmentioning
confidence: 99%